Pemberdayaan UMKM Kripik Landrang Indra Berbasis Digital - Ni Putu Nanik Hendayanti; Gusti Ayu Aghivirwiati; I Gusti Ayu Desi Saryanti; Siti Soraya (LPPM Universitas Bumigora, 2022)
The Ladrang Crispy Business of Mrs. Ni Kadek Indra Puspita is a home industry business located in Kenderan Village, Gianyar Regency. Indra's mother has been running the business of making ladrang chips for approximately 2 years since the onset of covid-19 which caused Indra's mother to be dismissed from work. During this 2 year period, the production of Ladrang Chips produced by partners is erratic every month depending on orders from small shops / stalls, which Indra usually entrusts to sell Ladrang chips which are produced by partners, and there are orders from relatives and partners, resulting in income uncertain partner. Customers owned by partners come from the partner's village of residence and there are also some from villages around the partner's residence. Therefore, the marketing area of ​​Mrs. Indra's Kripik Ladrang business is not wide. Based on this, the goal to be achieved in this community service activity is to help solve the problems faced by partners by helping to develop Instagram and Facebook marketing media, so that the businesses owned by partners are more easily known to the public. The result of this service is that Instagram and Facebook marketing media training can run well and smoothly and can achieve the expected results. Based on the results of the evaluation using a questionnaire, the results of the index category are very good with an index value of 92.5%.